Second Workshop on Digital Humanities and Natural Language Processing - Trojahn, Cassia (2022)
This proceedings brings together works presented at the Second Workshop on Digital Humanities and Natural Language Processing that took place in 21st of March 2022, along with the International Conference on the Computational Processing of Portuguese, PROPOR 2022. PROPOR is the main scientific meeting in the area of language and speech technologies for Portuguese and on the basic and applied research issues related to this language. As such it has a lot to offer and to learn from the Humanities. This workshop brought together 10 papers representing research in areas such as literature, linguistics, and history. All these topics were studied with the help of natural language processing techniques, models or tools. Each paper was reviewed by three collaborators from our program committee.